2000
DOI: 10.4049/jimmunol.165.8.4470
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Production and Molecular Diversity of Human Liver and Activation-Regulated Chemokine/Macrophage Inflammatory Protein-3α from Normal and Transformed Cells

Abstract: Liver and activation-regulated chemokine (LARC), also designated macrophage inflammatory protein-3alpha (MIP-3alpha), Exodus, or CCL20, is a C-C chemokine that attracts immature dendritic cells and memory T lymphocytes, both expressing CCR6. Depending on the cell type, this chemokine was found to be inducible by cytokines (IL-1beta) and by bacterial, viral, or plant products (including LPS, dsRNA, and PMA) as measured by a specific ELISA. Although coinduced with monocyte chemotactic protein-1 (MCP-1) and IL-8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 38 publications
3
73
1
1
Order By: Relevance
“…CCL20/LARC mRNA was previously detected in pancreatic adenocarcinoma cells and in epithelial cells of the appendix and of inflamed tonsils (37)(38)(39). In addition, CCL20/LARC protein was inducible in epidermal carcinoma cells (23). However, we found that the CCL7/MCP-3 and CCL20/LARC concentrations in ascitic fluid accompanying epithelial ovarian cancer remained below 0.5 and 0.4 ng/ml, respectively.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…CCL20/LARC mRNA was previously detected in pancreatic adenocarcinoma cells and in epithelial cells of the appendix and of inflamed tonsils (37)(38)(39). In addition, CCL20/LARC protein was inducible in epidermal carcinoma cells (23). However, we found that the CCL7/MCP-3 and CCL20/LARC concentrations in ascitic fluid accompanying epithelial ovarian cancer remained below 0.5 and 0.4 ng/ml, respectively.…”
Section: Discussioncontrasting
confidence: 48%
“…Chemokines and Chemokine Immunoassays-The chemokines CXCL8/IL-8, CCL2/MCP-1, and CCL20/LARC were quantified with specific ELISAs as described previously (23). The detection limits were 0.02, 0.1, and 0.04 ng/ml, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that IFN-γ inhibits MIP-3α production by both TNF-α and IL-1β. IL-1β and/or TNF-α induce MIP-3α in different cell types including keratinocytes, melanocytes, fibroblasts and monocytes [22,23,56], but the inhibitory effect of IFN-γ has not, to our knowledge, been previously described. On the contrary, IFN-γ induces MIP-3α protein expression in human keratinocytes [23], emphasizing the different regulation of chemokine expression in diverse cell types.…”
Section: Discussionmentioning
confidence: 77%
“…9,27,28 This combined constitutive/inducible profile is relatively unique among the chemokines, which, in turn, suggests a unique role for CCL20 in immune surveillance 15 and inflammation, as indicated by its upregulation in response to LPS. 29,30 and during infection (the present study).…”
Section: Discussionmentioning
confidence: 99%